Alternative designs and technological advancements of phase change material integrated photovoltaics: A state-of-the-art review. (April 2022) - Sharma, Manoj Kumar
Highlights: A structured overview of PCM integrated photovoltaics is presented. Various approaches to enhance the convection currents in PCMs are summarized. Effects of sun-tracking on PV module performance are discussed. Low-cost PCM obtained from petroleum waste can be used in PV/PCM systems. Thermoelectric integrated PV/PCM systems generate electricity during night-time. Abstract: Photovoltaics (PV) is the most established renewable energy technology of sunrays to electricity conversion, which converts only a fraction of the solar radiation to electricity. The remaining sunlight causes the heating of PV modules which significantly mitigates their performance and life-span. To minimize the temperature-dependent power degradations, various PV cooling techniques have been proposed in the literature. Utilisation of PCM as a cooling system is found an attractive way of photovoltaics thermal management. Present article demonstrates a state-of-the-art review of technological advancements of PCM integrated photovoltaics. Concentrated and non-concentrated PV modules integrated with PCM are discussed in detail. The extracted heat from PV panels is harnessed for domestic and industrial purposes through hybrid systems such as PCM integrated photovoltaic-thermal (PVT/PCM) systems and thermoelectric module integrated PCM regulated photovoltaic (PV/PCM-TE) systems. The effect of ambient temperature, sunlight intensity, PCM melting point temperature, PCM channel orientation, various heat transfer enhancement configurations, etc., on PV panel performance is studied. Moreover, a complete methodology for the numerical solution of a conventional PV/PCM system, along with the governing equations and boundary conditions, is discussed.